Intraoral and Extraoral Scanning Technologies in the Digital Workflow Era: An Integrative Review with Artificial Intelligence - Brunetto, Juliana Lujan [UNESP]; Ique, Manuel Martin Adriazola [UNESP]; de Moraes Melo Neto, Clovis Lamartine [UNESP]; Sachi, Victor Perinazzo [UNESP]; dos Santos, Daniela Micheline [UNESP]; Goiato, Marcelo Coelho [UNESP] (Universidad de Costa Rica, 2025)
The aim of this integrative review is to investigate the possibility of aligning three-dimensional intraoral scanner data with facial mobile device data, as well as comparing the effectiveness of AI-based search with manual search methods. This investigation adhered to the PRISMA guidelines aiming to answer the PICO question: “Does the facial and intraoral three-dimensional technologies are compatible and clinically applicable in oral rehabilitation?”. Was employed a search strategy incorporating specific keywords (dental, intraoral, photogrammetry, stereo photo, scanner, three-dimensional, stereophotogrammetry, scan, virtual articulators, facebow, face, facial) within multiple databases (Pubmed, BVS, and Scielo), including artificial intelligence (Scite.ai). Of the 7128 initially identified articles, 4 articles of manual search were included but none article of the artificial intelligence website were added. Among the most used: at the intraoral scanners were the TRIOS (3shape) (n=2) and for facial images the Apple Inc. cell phones (n=2). The most frequently reported software was Bellus3D (Bellus3D Inc.) with particular emphasis on the georeferencing tactic software. Several commonalities were observed, including the requirement for a 30cm spacing during cell phone-based extraoral scanning, the necessity for multiple captures, and the inclusion of landmarks and/or perioral and nasal scans. Manual searching is still the gold standard scientific searching data; Both stereophotogrammetry and mobile device scan can be used for facial scanning and the files can be integrated by utilizing georeferencing tactic software.
Tecnologías de escaneo intraoral y extraoral en la era del flujo de trabajo digital: una revisión integral con inteligencia artificial
Keywords: Artificial intelligence; Dental articulator; Photogrammetry; Temporomandibular joint; Three-dimensional imaging